The Impact of Knowledge Sharing In the Human Resource Capability - الطائي علي حسون; عليوي الهام محمد (Journal of Economics and Administrative Sciences, 2019)
Abstract The role of the independent variable and human resources capabilities was the role of the adopted variable. The aim of the research is to identify the level of participation in the knowledge of the organization through human resources and the rigorous scientific investigation to develop new mechanisms of action that help To manage the organization in the implementation of its mission and achieve its main objectives that have been found for it is to encourage the work of scientific research and maintain the preservation of its continuity to increase the competencies of knowledge, technical and skill to form a future workforce qualified to work In the sectors of society. In order to achieve the desired objectives, the main hypothesis was formulated to test the relationship between the variables of the research. The main hypothesis: There is a relationship of direct moral impact to the sharing of knowledge through its dimensions in the human resource capabilities. The research was applied to a sample of 162 employees of the Ministry of Science and Technology Research As a tool for collecting data, the research results in a set of results, the most important of which is the voluntary knowledge exchange of employees, the accumulation of knowledge and information, the free access to the information needed to accomplish the various tasks, and the encouragement of senior management of the organization’s employees.